Association of Human Rpel27, Rpel143 and Rpel41 with Nasopharyngeal Carcinoma - Chan, Stella Li Li (Universiti Malaysia Sarawak (UNIMAS), 2016)
Ribosomal proteins (RPs) are components of ribosome involved in ribosome biogenesis. Apart from their classical role, some of these RPs were reported to have extraribosomal functions such as deoxyribonucleic acid (DNA) replication, transcription and apoptosis. However, little is known about the role of RPs in tumorigenesis of nasopharyngeal carcinoma (NPC). Previous study has shown that ribosomal protein large subunit L27 (RPeL27), ribosomal protein large subunit L43 (RPeL43) and ribosomal protein large subunit L41 (RPeL41) showed differential expression in cell lines derived from NPC compared to nonnal epithelial (NPE) cell line. Here, the same three RPs were reported overexpressed in both transcript and protein level in five NPC cell lines in relative to one NPE cell line. The gene expression was relatively quantitated using real-time polyn1erase chain reaction (qPCR) while protein expression was detected using Western Blot (WB). Co-immunoprecipitation (co-IP) assay identified RPeL27 and RPeL43 interacting with POTE ankyrin domain family Eltubulin alpha-lA chain (POTEE/TUBAIA) and actin, cytoplasmic Ilbeta-actin-like protein 2 (ACTB/ACTBL2) complex endogenously in HKI while RPeL43 was reported interacting with eukaryotic translation initiation factor 2 subunit 1 (EIF2S 1) and muscle rat sarcoma viral oncogene homolog (MRAS). The differential expression ofthe three above mentioned RPs confinned their involvement in NPc. The identified interacting proteins with RPeL27 and RPeL43 has suggested possible mitogen-activated protein kinase/extracellular signal-related kinase (MAPKIERK) pathway in NPC metastasis.